Faktor Pembentuk Kesejahteraan Psikologis pada Milenial - Hari Slamet Trianto; Christiana Hari Soetjiningsih; Adi Setiawan (Philanthropy: Journal of Psychology, 2020)
The disruption era brought many changes to the millennial generation. The development of science is one of the reasons for this change. The main players in this era are millennials. Given the demographic bonus that Indonesia will find, where productive millennials will have a larger number than those of non-productive ages, the welfare of millennials deserves attention, especially their psychological well-being. For this reason, this research will examine in depth the factors that shape millennial psychological well-being. By knowing these factors, it can provide suggestions so that the psychological well-being of millennials can be maintained and improved. This research was conducted by interviewing productive and working millennials so that the data related to their psychological well-being can be obtained. Based on the research conducted, it was found that there are at least five factors that influence the psychological well-being of millennials. These five factors can be said to be interconnected and separate in shaping the psychological well-being of millennials.